(untitled) (Altre Modernità, 2015)
TV has played a fundamental role in unifying Italy and the Italian language (cfr. D’Achille 2006: 225; cfr. Maggini 2011: 131) and has recently turned into a medium for linguistic and cultural globalization and colonization. As a consequence, dubbing and “doppiaggese” (a sort of Italian equivalent of dubbese, though carrying a negative connotation) have assumed crucial importance in the evolution of the Italian language, especially if we consider that the great majority of TV products broadcast in Italy are dubbed from English. “Doppiaggese” is not only the language of bad or unskilled dubbing from English into Italian, but also a significant component of the language of fictional TV programs in Italian itself, which often unintentionally use scripts full of calques and influence the everyday spoken and written discourse of Italian speakers. The aim of the present article is to open a window on the mutation undergone by the Italian language often due to inaccurate dubbing, the so-called “doppiaggese”. By taking into consideration the research and surveys carried out by the present writer on some cases of interference (cfr. Sileo 2010 and Sileo 2012), this study aims to convey the image of AVT translation as a window which puts two different linguo-cultural systems in contact and influences the target language system.